Penerapan Model Connected Dengan Pendekatan Berbasis Masalah Pada Matakuliah Pendidikan Kewarganegaraan - Harry Surahman; Endang Setyowati (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
This study aims to describe the application of the connected model with the MK Citizenship Education problem-based approach to improve critical thinking skills (1) to describe student activities while attending lectures using the connected model with a problem-based approach; (2) describe student responses after applying the connected model with a problem-based approach. The research design is classified as experimental research with a two group pretest-posttest research design. The research subjects were Indonesian Language and Literature Education Study Program Students class of 2022 with a total of 25 students for each experimental class and control class. Instruments used to collect data include questionnaires, learning achievement tests, observation, and documentation. Data analysis using SPSS 17 software program. Based on the results of inferential statistical analysis, it was found that there was a significant difference between the increase in student learning outcomes in the experimental class and the control class. In more detail, the research results were obtained as follows: (1) The results of the activities of students who took part in connected model lecture activities with a problem-based approach were better than students who took conventional lectures; (2) Students give a positive response to the application of the connected model; Based on these findings, it can be concluded that the connected model with a problem-based approach can improve the critical thinking skills of Indonesian Language and Literature Education Study Program students.